Next Generation of Transport Networks - AK Sparks; L Tancevski (Dianxin kexue)
Telecommunications transport networks carry aggregated communications information transparently, reliably and efficiently,supporting a full range of communications service provider（CSP）services and service networking layers （IP,Ethernet,ATM,TDM,etc.）. While optical-specific technology advances will continue to be essential for continued scalability and cost/bit advances,it is asserted here that a combination of external drivers will have the greatest impact on shaping the form of the next generation of transport networks. The converging drivers for change were discussed, a vision of how the broader network architecture as well as transport networks change was laid out, and the changing network attributes and technology directions central to this transformation were illustrated.